Implementasi Kurikulum Muatan Lokal Keagamaan Dalam Pengembangan Sikap Sosial Dan Spiritual Di SMA Al Azhar Menganti Gresik - Moh Misbahul Munir; Mohammad Anas Ma'arif (Jurnal Pendidikan Agama Islam Miazhar, 2023)
The decline in students' morale and social attitudes is one of the current educational problems, one of the efforts of Al Azhar High School to replace it which is also under the auspices of the Darul Ihsan Islamic Boarding School in developing students' social and spiritual attitudes by implementing a local religious content curriculum. This study discusses the application of the local religious content curriculum and its impact on the development of social and spiritual attitudes at Al Azhar Menganti High School. The formulation of the problem in this study includes a descriptive analysis type of research using a qualitative approach. Meanwhile, data collection techniques in this study used observation, interview, and documentation techniques. While the data analysis technique used is descriptive qualitative. The results of the research that has been conducted regarding the implementation of the religious local content curriculum and its impact on the development of spiritual attitudes and social attitudes at Al Azhar Menganti High School show that the implementation of the religious local content curriculum is in accordance with the rules of the independent curriculum which are adapted to school policies and by adding activities. religious support. Meanwhile, the application of the religious local content curriculum has an impact on the development of social attitudes and spiritual attitudes of students, including increasing student piety in worship, politeness to teachers and friends, and so on. While the supporting factors for implementing the local religious content curriculum include full support from the entire school community as well as under the auspices of Islamic boarding schools, of course supporting religious activities, and the inhibiting factors include the lack of religious infrastructure, lack of parental support, and lack of students' ability to religious.